2011
DOI: 10.1152/ajpregu.00784.2010
|View full text |Cite
|
Sign up to set email alerts
|

End-tidal carbon dioxide tension reflects arterial carbon dioxide tension in the heat-stressed human with and without simulated hemorrhage

Abstract: End-tidal carbon dioxide tension (PetCO2) is reduced during an orthostatic challenge, during heat stress, and during a combination of these two conditions. The importance of these changes is dependent on PetCO2 being an accurate surrogate for arterial carbon dioxide tension (PaCO2), the latter being the physiologically relevant variable. This study tested the hypothesis that PetCO2 provides an accurate assessment of PaCO2 during the aforementioned conditions. Comparisons between these measures were made: 1) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…It has been recently demonstrated that Pa CO 2 and PET CO 2 are similar over a range of hypocapnic and hypercapnic stimuli and respiratory rates [9]. PET CO 2 has also been shown to accurately reflect Pa CO 2 during whole body HS alone and during a simulated hemorrhage challenge [2]. Thus, in the current study PET CO 2 is an accurate index for Pa CO 2 .…”
Section: Discussionmentioning
confidence: 51%
“…It has been recently demonstrated that Pa CO 2 and PET CO 2 are similar over a range of hypocapnic and hypercapnic stimuli and respiratory rates [9]. PET CO 2 has also been shown to accurately reflect Pa CO 2 during whole body HS alone and during a simulated hemorrhage challenge [2]. Thus, in the current study PET CO 2 is an accurate index for Pa CO 2 .…”
Section: Discussionmentioning
confidence: 51%
“…Specifically, while normothermic, during conditions where venous return is compromised (like LBNP), the reduction in overestimates the reduction in arterial CO 2 partial pressures (Immink et al 2006 a , b ; Serrador et al 2006). However, during LBNP while heat stressed, decreases in accurately track decreases in arterial CO 2 partial pressures (Brothers et al 2011). The net result is that there are similar values between thermal conditions during LBNP, even though ventilation is generally higher throughout this perturbation while heat stressed.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary VO 2 , carbon dioxide elimination (VCO 2 ), VE, respiratory frequency (Rf), end‐tidal partial pressure of O 2 (PETO 2 ), and end‐tidal partial pressure of CO 2 (PETCO 2 ) were measured with the breath‐by‐breath cardiopulmonary system at 10%, 30%, 50%, 70%, 90%, and 100% of work completed. Given that direct measurements of PaCO 2 were note performed, PETCO 2 was used to estimate changes in PaCO 2 as it has been shown to accurately predict direct measurements of PaCO 2 at graded levels of hyper‐ and hypocapnia (Willie et al., ) and hyperthermia (Brothers et al., ; Nelson et al., ). Mean arterial pressure (MAP) was recorded manually by the same investigator using a sphygmomanometer (Gamma G5, Heine Optotechnik, Herrsching, Germany) and calculated as: DBP + 1/3 × (SBP − DBP), where DBP is diastolic blood pressure and SBP is systolic blood pressure.…”
Section: Methodsmentioning
confidence: 99%